(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2024)
Ngeholi is one of the traditions practiced in many regions across Indonesia. However, Penerokan stands out as a village that has its own distinct features in the way this tradition is carried out, making it different from other regions. The research approach used is qualitative descriptive field research. The goal of this type of research is to obtain a comprehensive description of a particular phenomenon, based on the perspectives of those being studied. Using the Miles and Huberman model, the steps of data analysis include data reduction, data presentation, and drawing conclusions/verification. The findings of this study reveal that this tradition has been carried out for a long time by the elders of Penerokan village. The Ngeholi tradition is a custom passed down through generations by the people of Penerokan, brought by their ancestors, and it continues to be preserved to this day without any set time limits for its preservation. They believe that this tradition must be maintained, as it is considered important for both the wealthy and the average person to commemorate someone’s death, reminding themselves that this world is temporary, while the hereafter is eternal. The author recommends that the residents of Sekarsari Hamlet, KM 49, continue to preserve the Ngeholi tradition, as it offers a valuable cultural display for those outside of Penerokan, reflecting its unique characteristics.